Koneksi Politik, Gender Diversity, Inovasi dan Kesadaran Kewajiban Pajak Perusahaan - Nugroho, Wawan Cahyo (E-Jurnal Akuntansi; Vol 33 No 10 (2023)DO - 10.24843/EJA.2023.v33.i10.p06, 2023)
This research aims to test and analyze the influence of political connections, gender diversity, and innovation on corporate tax obligations. This research used 315 samples from 45 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2021. Technical data analysts use multiple linear regression. The research results show that political connections do not have a significant effect on tax compliance because manufacturing companies want to maintain good relations with stakeholders, by being obedient and obedient in fulfilling their tax obligations without taking advantage of political connections. Gender diversity has a significant positive effect on tax compliance because women have the spirit of minimizing risks, avoiding fraud, obeying regulations so that it will lead to positive actions in taxpayer compliance. Innovation has a significant positive effect on tax compliance because companies can make innovation an effort to improve product quality which results in company expenses increasing and profits generated by the company decreasing and resulting in tax avoidance or decreased tax compliance. Keywords: Political Connections; Gender Diversity; Innovation and Tax Compliance